The equality of religions: a preliminary response - Abdullah, Fatimah (International Islamic University Malaysia, 2010)
Different religion perceives Truth differently and conceptions of that Truth may even be tangential, let alone identical. Islam is both exclusive and inclusive. As far as theological or creedal matters are concern, Islam is exclusive. The creedal matters pertaining to question of God, His nature or attributes, Muslims should not compromise with conception or perception of other religions, except in a very general rubūbiyyah manner. In other word, we cannot dilute the concept of God with that of other religions. As for moral and ethical values, the door is wide open for polite conversation, dialogue and cooperation. In fact, noble ethical principles of interpersonal relationship found in most religious teachings serve as source of guidance for human relationship. For the crux of all religions are peace, balance and harmony not violence and aggression. The concept of universalism in the religion of Islam manifests itself in inclusively aspect of its teaching particularly in dealing with other religion adherents. Even though Islam is exclusive towards its unique tawḥīd, however the treatment is based on the humanity that is to make no distinction between all different nations as the creations of God. Therefore, there is no such thing to discriminate or degrade others since all are Gods creations that receive blessings or graces from Him alone. In this respect, Islam comes out with several principles deal with the diversity of religion or belief as well as race and nations.